2018
DOI: 10.2135/cropsci2018.02.0099
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Advance in Grain Yield and Other Traits in Two Tropical Maize Composites Developed via Reciprocal Recurrent Selection

Abstract: Assessment of genetic gain in two tropical maize (Zea mays L.) composites improved across years is critical in determining their future improvement and use as sources of inbred lines. Two genetically complementary tropical maize composites were subjected to four cycles of reciprocal recurrent selection (RRS) for grain yield, resistance to foliar diseases, and other desirable agronomic traits using a reciprocal S1 testcross evaluation scheme. The objectives of this study were to evaluate the effects of this sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The Delta method was used to compute the standard errors as proposed by Holland (2006). The genotypic correlation greater than twice the value of its standard error was considered to be significant statistically (Kolawole et al, 2018)…”
Section: Data Collectionmentioning
confidence: 99%
“…The Delta method was used to compute the standard errors as proposed by Holland (2006). The genotypic correlation greater than twice the value of its standard error was considered to be significant statistically (Kolawole et al, 2018)…”
Section: Data Collectionmentioning
confidence: 99%
“…Maize (Zea mays l.) is a staple cereal crop in Africa (Musundire et al 2021) with increasing demand as food, animal feed and industrial products in nigeria (Olaniyan 2015;kolawole et al 2018). the ever-increasing human population and demand led farmers in diverse agro-ecological zones of nigeria to the cultivation of various maize genotypes with yield increase over open-pollinated varieties viz., synthetics, composites, non-conventional maize hybrids (top-cross, double top-cross, and va-rietal cross), and conventional maize hybrids (single, three-way and double-cross).…”
mentioning
confidence: 99%
“…In an RGS breeding program in wheat for the less complex trait grain fructans compared to grain yield, significant genotype-by-environment interactions were observed with little effects on prediction accuracies (Veenstra et al, 2020). In contrast, in an RRS program in tropical maize focusing on grain yield, Kolawole et al (2018) also observed that genotype-by-environment interactions negatively affected the observed response to selection.…”
Section: Discussionmentioning
confidence: 89%
“…Recurrent selection cycles are applied to further manifest this tendency. The success of RRS has been demonstrated in outcrossing species such as maize (Eyherabide and Hallauer, 1991;Tardin et al, 2007;Souza et al, 2010;Kolawole et al, 2018) and sugar beet (Doney and Theurer, 1978;Hecker, 1985). To the authors knowledge, no studies were published that investigate the potentials and limits of RRS in autogamous cereals such as wheat.…”
Section: Introductionmentioning
confidence: 99%